Formative assessment, work regulation, organization, engagement, tracking and attendance in Spanish Universities - Hortigüela Alcalá, David; Fernández Río, Javier; Castejón Oliva, Javier; Pérez Pueyo, Ángel (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2017)
The Assessment Systems Scale, a 34-item questionnaire, has been proven a robust, reliable and valid instrument to evaluate assessment procedures at the university level. However, the sample used to validate it was rather small, and proper validation of instruments requires testing on multiple independent samples. The current studies evaluated the reliability and the validity of a reduced version consisting in only 23 items, as well as its interactions. Study 1 determined the validity and reliability of the reduced version of the Assessment System Scale in the context of a large sample of Spanish university students. 3.428 students and 52 teachers from 17 different universities across Spain agreed to participate. Results showed a 3-factor structure and high internal consistency (α = .835). In Study 2 descriptive and inferential statistics showed that formative assessment significantly linked students’ work regulation and organization, engagement, tracking and attendance. Students who participate in formative assessment systems understand how necessary is class attendance, because it favors greater engagement and, as a consequence, better regulation and monitoring of the content throughout the teaching-learning process. A significant relationship between peer review and more effective feedback to improve the understanding of the tasks found. Moreover, the definition of clear evaluation criteria correlated positively with the registration of individual work or group. A level of self-regulation work differently depending on the degree studied was found. We conclude that it is necessary to implement formative assessment systems using tools and systematic procedures that ensure truly an alternative to more traditional methodological approaches